Respuestas
Respuesta dada por:
11
=> x+y=4
x=4-y
=> 2x-3y=3
2x=3+3y
Reemplazamos "x" :
2x=3+3y
2(4-y) =3+3y
8-2y =3+3y
8-3 = 3y+2y
5=5y
1=y
Hallamos "x" :
x=4-y
x=4-1
x=3
Espero te sirva !! ^^
x=4-y
=> 2x-3y=3
2x=3+3y
Reemplazamos "x" :
2x=3+3y
2(4-y) =3+3y
8-2y =3+3y
8-3 = 3y+2y
5=5y
1=y
Hallamos "x" :
x=4-y
x=4-1
x=3
Espero te sirva !! ^^
REGINAGPE:
gracias si me ayudo pero lo que yo quiero es hacerla por el metodo grafico
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años